2016
DOI: 10.3390/en9040283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biomass Physical Properties on Top-Lit Updraft Gasification of Woodchips

Abstract: Abstract:The performance of a top-lit updraft gasifier affected by biomass (pine wood) particle size, moisture content and compactness was studied in terms of the biochar yield, biomass burning rate, syngas composition and tar content. The highest biochar yield increase (from 12.2% to 21.8%) was achieved by varying the particle size from 7 to 30 mm, however, larger particles triggered tar generation that reached its maximum of 93.5 g/m 3 syngas at 30-mm biomass particles; in contrast, the hydrogen content in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
1
42
1
Order By: Relevance
“…Specifically, as fuel MC increases from 20% to 35%, CO concentration has a pronounced drop and this leads to a reduction in the syngas HHV. While our results indicate a mild decrease in H2 and CH4 content with an increase in fuel MC, Atnaw et al [21] and James et al [22] reported marginal or negligible changes in H2 and CH4, though Li et al [19] observed a decrease, and Paasen and Kiel [20] found a modest increase in H2. The increase in CO2 concentration with increasing MC is similar to findings by Huang et al [8].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Specifically, as fuel MC increases from 20% to 35%, CO concentration has a pronounced drop and this leads to a reduction in the syngas HHV. While our results indicate a mild decrease in H2 and CH4 content with an increase in fuel MC, Atnaw et al [21] and James et al [22] reported marginal or negligible changes in H2 and CH4, though Li et al [19] observed a decrease, and Paasen and Kiel [20] found a modest increase in H2. The increase in CO2 concentration with increasing MC is similar to findings by Huang et al [8].…”
Section: Discussioncontrasting
confidence: 74%
“…Lower CO concentration was observed at higher fuel moisture content, but the changes in H 2 and CH 4 concentrations were only marginal; syngas calorific value almost doubled within the range of 2.5-6.0 MJ/Nm 3 as biomass moisture content was reduced from 29% to 22% wb. James et al [22] assessed the effect of biomass physical properties on updraft gasification of woodchips. The H 2 content was found to have no significant changes while the CO content was somewhat reduced as the moisture content increased from 10% to 22% wb, resulting in a decrease in the higher heating value of the syngas from 3.67 to 2.84 MJ/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These stoves may be used for cooking but also have the possibility to be used as a gasifier for producer gas generation or charcoal generation. The producer gas may be used for heating or for power production [9] in an engine.…”
Section: Introductionmentioning
confidence: 99%
“…At this boundary they recorded the percent of the original fuel mass consumed. Typically 70% to 85% of the original fuel mass was consumed indicating that the char mass left at the end of gasification was 15% to 30% of the fuel mass [9].…”
Section: Introductionmentioning
confidence: 99%
“…In [38], the behavior of different biomasses (wood, torrefied biomass, agricultural and industrial wastes) after gasification in a bubbling fluidized bed gasifier at mild temperatures (600 • C) was investigated, using an air-steam mixture at different stoichiometric ratios. The low-temperature gasification of biomass in a purpose-built atmospheric bubbling fluidized bed reactor was optimized on the basis of the experimental results; it was found that the same gasification conditions (steam quantity) do not affect every biomass in the same way, and gasification conditions must be carefully tested for each biomass.…”
Section: Gasification Technologies and Modelling Approachesmentioning
confidence: 99%